Eksistensi Guru dalam Meningkatkan Kualitas Pembelajaran di Madrasah Ibtidaiyah Manggarupi Gowa: Teacher's Existence in Improving the Quality of Learning in Madrasah Ibtidaiyah Manggarupi Gowa - Afia, Selfa; Achruh, Andi; Rosdiana, Rosdiana (CV. Kalimasada Group, 2023)
This article aims to determine the duties and obligations of teachers as professional educators. Descriptive qualitative methodology was used with a field study at Madrasah Ibtidaiyah Manggarupi Gowa South Sulawesi. The research findings show that MI Manggarupi teachers view themselves as agents of change who must constantly develop new teaching strategies and modify the curriculum to meet the needs of their students. To produce comprehensive learning experiences, this task requires active participation in professional growth, application of technology, and cross-disciplinary collaboration. Overall, our findings emphasize the importance of capable educators and leadership in improving teaching standards in educational institutions. The teaching personnel at MI Manggarupi use comprehensive teaching methods that integrate academic, moral and religious principles. Cooperation between educators and schools is crucial to improving teaching standards. Using a comprehensive approach, they collaborate to create lesson plans, incorporate various teaching modalities and modify the curriculum to meet students' needs.